Systematic Review: Mechanism of Ginger (Zingiber offinale) as Anti-inflammatory - Dwi Monika Ningrum; Denih Agus Setia Permana; Atri Sri Ulandari (Jurusan Farmasi Fakultas Kedokteran Universitas Lampung, 2025)
The appearance of inflammation is a hallmark of a large number of human diseases, ranging from infection to neurodegeneration. In the treatment of inflammation, a group of drugs that are widely given are non-steroidal anti-inflammatory drugs (NSAIDs). Long-term use of NSAIDs can result in various side effects, namely gastrointestinal disorders, damage to the kidneys, and cardiovascular disorders. Given the side effects that can be caused by the use of NSAIDs, other alternatives are needed to overcome and reduce inflammation. One of the plants that can be used to treat inflammation is ginger. This journal review was conducted by reviewing electronic journals related to the use of ginger as an anti-inflammatory mechanism with the study report method. The inclusion criteria used include ginger as an anti-inflammatory, journals from 2008-2012, journals are scientific journals, in vitro and in vivo, free full text, while the exclusion criteria are the benefits of ginger not as an anti-inflammatory. Ginger as an anti-inflammatory has several mechanisms including inhibiting macrophage activation, increasing endogenous antioxidant activity, inhibiting the production of PGE2, tumor necrosis factor α (TNFα), and cyclooxygenase. Inhibition of cyclooxygenase is selective only for COX-2 activity. COX-1 inhibition is associated with gastrointestinal irritation, selective inhibition of COX-2 will help minimize side effects.